The geological setting of Matra ore deposit (France): insights from lithostratigraphy and polyphase deformation history - Danis Ionut Filimon; Giacomo Vannucci; Alessandro La Rosa; Vincenzo Zarone; Maria Di Rosa (Journal of Maps)
Arsenic sulfide mineralization in Matra mine (southern Alpine Corsica) is hosted by two tectonic units belonging to the Schistes Lustrés Complex. Country rocks include a Jurassic ophiolitic sequence and related sedimentary covers, which were metamorphosed. Geological mapping and thin section analysis were used to understand lithostratigraphy and the tectononic-metamorphic history. The polyphase deformation history includes four phases of ductile deformation during the Late Cretaceous–Early Oligocene Alpine orogeny, with associated high-pressure–low-temperature metamorphism culminating in eclogite facies. The post-Alpine phase includes an N–S extensional fault system that controls the movement of ore fluids.